Accuracy of Blood Loss Measurement during Cesarean Delivery - Doctorvaladan, Sahar V.; Jelks, Andrea T.; Hsieh, Eric W.; Thurer, Robert L.; Zakowski, Mark I.; Lagrew, David C. (American Journal of Perinatology Reports, 2017)
Objective This study aims to compare the accuracy of visual, quantitative gravimetric, and colorimetric methods used to determine blood loss during cesarean delivery procedures employing a hemoglobin extraction assay as the reference standard.Study Design In 50 patients having cesarean deliveries blood loss determined by assays of hemoglobin content on surgical sponges and in suction canisters was compared with obstetricians' visual estimates, a quantitative gravimetric method, and the blood loss determined by a novel colorimetric system. Agreement between the reference assay and other measures was evaluated by the Bland–Altman method.Results Compared with the blood loss measured by the reference assay (470 ± 296 mL), the colorimetric system (572 ± 334 mL) was more accurate than either visual estimation (928 ± 261 mL) or gravimetric measurement (822 ± 489 mL). The correlation between the assay method and the colorimetric system was more predictive (standardized coefficient = 0.951, adjusted R2 = 0.902) than either visual estimation (standardized coefficient = 0.700, adjusted R2 = 00.479) or the gravimetric determination (standardized coefficient = 0.564, adjusted R2 = 0.304).Conclusion During cesarean delivery, measuring blood loss using colorimetric image analysis is superior to visual estimation and a gravimetric method. Implementation of colorimetric analysis may enhance the ability of management protocols to improve clinical outcomes.
Keywords: cesarean delivery; blood loss measurement; postpartum hemorrhage; quality improvement